1999
DOI: 10.1021/la981179i
|View full text |Cite
|
Sign up to set email alerts
|

On the Adsorption Kinetics of Octanoic Acid at the Mercury/Electrolyte Interface

Abstract: The adsorption kinetics of octanoic acid at the mercury/electrolyte interface was investigated by means of capacity−time transients. For low concentrations of octanoic acid and for the short-term region, the transients can be theoretically well described with a diffusion-controlled adsorption process according to the Delahay−Trachtenberg law. The long-term transients for higher concentrations of octanoic acid exhibit an increase of the capacity with time, which can be modeled with an adsorption-controlled repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 18 publications
1
35
0
Order By: Relevance
“…Recently, investigations with atomic force microscopy (1-9), STM (10), spectroelectrochemical methods (11), grazing incident X-ray diffraction pattern (12), and electrochemical methods (13)(14)(15) have shown that surfactant molecules adsorbed at the solid-solution or air-water interface form aggregates and that surface aggregate phase transitions occur.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, investigations with atomic force microscopy (1-9), STM (10), spectroelectrochemical methods (11), grazing incident X-ray diffraction pattern (12), and electrochemical methods (13)(14)(15) have shown that surfactant molecules adsorbed at the solid-solution or air-water interface form aggregates and that surface aggregate phase transitions occur.…”
Section: Introductionmentioning
confidence: 99%
“…The surface concentration of such hemimicelles should be proportional to that of octanoic acid as well as that of the anion, so leading to the asymmetry in the adsorption behavior observed and to the growing tendency to form such hemimicelles if the specific adsorption of the anion increases. The increase in the capacity is then only a logical consequence of the hemimicelle formation as we already stated in our last paper on octanoic acid (24).…”
Section: C Vs T Curves: Effect Of the Supporting Electrolyte Concmentioning
confidence: 65%
“…In investigations of the kinetics of the adsorption of neutral organic molecules it is customary to start from a potential where there is no or negligible adsorption. Thus, no molecules of octanoic acid exist in the double layer (24).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations